Sobrevida e fatores associados ao óbito em crianças, adolescentes e adultos jovens soropositivos para HIV por transmissão vertical - Dias, Jucielma de Jesus (2015)
Objective: To analyze the survival and factors associated with death in children, adolescents and young adults infected with HIV through vertical transmission, enrolled in the Municipal Reference Center (CRM) STD / HIV / AIDS Feira de Santana. Methods: An observational, longitudinal study, developed from a cohort of HIV-positive to HIV, infected by vertical transmission from secondary data obtained from the review of clinical records of 37 children, 21 adolescents and five (5) young adults, ranging age between 0 and 24 years enrolled in the Specialized Care Service (SAE) of CRM, from 2003 to 2014. In the analyzes we used Pearson X2 test, exact Fisher test and its value p, to investigate factors associated with death. In addition, it used survival analysis with construction of Kaplan-Meier curves and log-rank test to verify statistically significant association between groups of variables listed. Finally, we used regression Cox proportional hazards to estimate adjusted risk factors for death. Results: There was a predominance of groups of 0-12 years (58.7%) and 13-19 years (33.3%), female (52.4%) and black / mulatto (71.8%). Most of the study population made use of ART (71.4%), 82.5% had no comorbidities and 65.1% were not affected by non-oral opportunistic infections, though, 85.7% had at least one episode oral candidiasis. . Of the subjects studied, 71.4% were alive at the end of the follow-up period; 23.8% had AIDS as a cause death and three 4.8% patients died from other causes. Risk factors associated with death highlighted the variables "age" (p = 0.02), "non-oral opportunistic infection" (p = 0.00), " oral candidiasis "(p = 0.00)," CD4 "(p = 0.03). Survival analysis showed reduction in the probability of survival time only for individuals who came to the service with CD4 cell counts less than 350 cells / mm 3 (p = 0.00). The median overall survival time was 8.8 years, and the individuals using HAART had a higher survival (10.6 years) compared to those who have not used antiretroviral (6.0 years). In the multivariate analysis, statistically significant variables were age (<13 years), behaving as a protective factor (HR: 0.88; 95% CI: 0.78 to 0.98) and non-oral opportunistic infection as a factor of risk of death (HR: 4.3; 95% CI 1.51 to 12.1). Conclusion: This study points to the increased survival among infected by vertical route, evidenced by the significant number of individuals who have reached adolescence and possibly this is due to the use of antiretroviral with longer survival time among those who used the therapy, which shows that good results can be achieved, even in countries with limited resources. Causes of death resembled the national standard, although this is in transition, considering the causes unrelated to AIDS. The opportunistic infection remained a risk factor for death, according to the literature. The results show continuing need for adjustments and developments, in order to deal with the challenge of a chronic infection among individuals in a vulnerable stage, own youth.